Systematic Review and Meta-Analysis of Prevalence of Depression Among Caregivers of Cancer Patients - Pan, Yuan-Chien; Lin, Yaw-Sheng (Frontiers in Psychiatry, 2022)
Background: Caregivers of cancer patients commonly experience depressive symptoms due to the heavy burden of caregiving responsibility. Objective: This meta-analysis examined the prevalence of depression among caregivers of cancer patients. Methods: We included 85 studies covering 23,317 participants published between 2001 and 2021 (25 countries) that reported the prevalence of depression among caregivers of cancer patients. We examined the pooled prevalence of depression and hypothesized moderators, including year, age, sex, geographic regions, percentage of spousal caregivers, depression measures, and cancer stage. Results: All 85 effect sizes included 6,077 caregivers of patients with depression. The weighted average prevalence of depression was 25.14% (95% CI, 21.42%–29.27%) among caregivers. The prevalence rates were moderated by geographic region, patients’ cancer stage, and measures for depression. Prevalence rates also varied among the different measures assessing depression. The prevalence rate decreased with the mean age of caregivers and the percentage of spousal caregivers. Conclusions: This study revealed a high prevalence of depression among caregivers of cancer patients. The prevalence rates also varied with the study design, demographics of caregivers, and patients’ medical information. These findings highlight that psychological support and intervention may be crucial for patients and their caregivers in clinical practice.